Heterotrophic algal production method - Ariff, Arbakariya; Azma, Mojtaba; Mohamed, Mohd. Shamzi; Abdul Rahim, Raha; Mohamad, Rosfarizan; Kapri, Mohammad Rizal (2011)
The present invention discloses a method for the purification and cultivation of microalgae, in which the method is capable of achieving high microalgae cell density with high lipid content. Accordingly, the method comprises the steps of: (i) preparing an axenic culture of a microalgae strain, in which the strain is purified through a series of effective physical and chemical treatment for the removal of contaminants from the microalgae strain; (ii) subjecting the axenic culture to heterotrophic conditions to produce heterotrophic cells; and (iii) culturing the heterotrophic cells under conditions to promote accumulation of microalgae biomass concentration and lipid content.